Anesthetic approach of a patient with acute left-branch block - Marcelino Sánchez Tamayo; Maribel Correa; Miguel Livan Sánchez Martín; Eivet García Real (Revista Cubana de Anestesiología y Reanimación, 2018)
Introduction: Rate-dependent left bundle branch block is not a rare entity for the clinical practice in anesthesiology, but appears as a consequence of heart diseases or not always due to slowness in atrial frequency above all, with coronary artery diseases diagnosed only after their being ruled out. Objective: To describe the clinical-anesthetic management of a patient who presented left bundle branch block for elective thoracic surgery due to mediastinal tumor. Findings: We present a clinical case of a female patient with rate-dependent left bundle branch block who was announced for thoracic surgery, without a previous history of coronary artery disease. The surgery proceeded without complications and with positive outcome. Conclusions: Rate-dependent left-branch block is a rare entity and a diagnosis ruling out other cardiovascular entities or not, such as myocardial ischemia. An adequate intraoperative management of the patient provides excellent outcome without clinical translation or complications.